Intraperitoneal And Incisional Bupivacaine Analgesia For Major Abdominal/Gynecologic Surgery: A Placebocontrolled - R. Azarfarin; M. Jafari Shobeir; S. Atashkhoii (Medical Journal of The Islamic Republic of Iran, 2006)
Background:Postoperative pain is an important surgical problem. Recent studies in pain pathophysiology have led to the hypothesis that with perioperative administration of analgesics (pre-emptive analgesia) it may be possible to prevent or reduce postoperative pain. This study was planned to investigate the efficacy of pre-emptive analgesia on postoperative pain after major gynecologic abdominal surgeries. Methods: In this prospective, double-blinded, randomized, and placebocontrolled trial, 60 ASA physical status I and II patients undergoing major abdominal gynecologic surgeries were randomized to receive 45 mL of bupivacaine 0.375% or 45mL of normal saline; 30 mL and 15 mL of the treatment solution was administered into the peritoneal cavity and incision, respectively, before wound closure. The pain score of the patients was evaluated by the visual analogue scale (VAS) on awakening, and at 6, 12, and 24h after surgery. Time to first analgesia request and total analgesic requirements in the first 24h were recorded. Results: Pain scores were significantly higher in the placebo group than in the bupivacaine group on awakening (5.98±1.01 v.s 1.05±1.05; p<0.001), and at 6h after surgery (5.37±0.85 vs. 2.51±1.02; p<0.001). First request to analgesia was significantly longer in the bupivacaine patients than in the placebo group (5.87±3.04 h vs.1.35±0.36; p<0.001).Meperidine consumption over 24h was 96.00 ±17.53 mg in the placebo group compared with 23.28 ±14.89 mg in the bupivacaine patients (p<0.001).Conclusion:A combination of intraperitoneal and incisional bupivacaine infiltration at the end of abdominal gynecologic surgeries reduces postoperative pain on awakening and for 6 hours after surgery, and provides significant opioidsparing analgesia for 24 h after gynecologic abdominal surgeries.